Effects of raw red onion consumption on metabolic features in overweight or obese women with polycystic ovary syndrome: A randomized controlled clinical trial. Issue 4 (10th March 2014) - Ebrahimi‐Mamaghani, Mehranghiz; Saghafi‐Asl, Maryam; Pirouzpanah, Saeed; Asghari‐Jafarabadi, Mohammad
Abstract Aim We aimed to evaluate the effects of raw red onion consumption on metabolic features in overweight and obese women with polycystic ovary syndrome. Material and Methods In this randomized controlled clinical trial, the patients (n = 54) were randomly allocated to the intervention group as 'high‐onion' (raw red onions: 2 × 40–50 g/day if overweight and 2 × 50–60 g/day if obese) or to the control group as 'low‐onion' (raw red onions: 2 × 10–15 g/day) along with limited liliaceous vegetables for 8 weeks. Body mass index, dietary record, and metabolic parameters (fasting blood sugar, triglycerides, total cholesterol, low‐density lipoprotein cholesterol, high‐density lipoprotein cholesterol, and lipoprotein (a)) were evaluated in the follicular phase of the menstrual cycle at baseline and after 8 weeks. Hormonal variables (progesterone, prolactin, and 17‐OH progesterone) were also measured at baseline. Results Onion significantly decreased the levels of total cholesterol within each group; however, these changes were stronger in the high‐onion group (weighted mean differences [WMD]: −5.60 [95% confidence interval [CI]: −9.16, −2.03]; P = 0.003) than in the low‐onion group (WMD: −6.42 [95%CI: −11.97, −0.87]; P = 0.025). Similarly, low‐density lipoprotein cholesterol decreased significantly (WMD: −5.13 [95%CI: −9.46, −0.81); P = 0.022) in the high‐onion group, and (WMD: −2.90 [95%CI −5.57, −0.21]; P = 0.035) in the low‐onion group after treatment. The levels of fasting blood sugar, triglycerides, high‐density lipoprotein cholesterol and lipoprotein (a) did not differ significantly after 8‐week onion treatment. Adjustment for confounders did not make any significant changes in any of the parameters in post‐treatment levels. Conclusion Raw red onion consumption appears to be effective as a cholesterol‐lowering food agent in women with polycystic ovary syndrome. However, further investigation is warranted.